Near Real-Time Measurement of Snow Water Equivalent in the Nepal Himalayas - Kirkham, James D.; Koch, Inka; Saloranta, Tuomo M.; Litt, Maxime; Stigter, Emmy E.; Møen, Knut; Thapa, Amrit; Melvold, Kjetil; Immerzeel, Walter W. (Frontiers in Earth Science, 2019)
Seasonal snow is an important component of the Himalayan hydrological system, but a lack of observations at high altitude hampers understanding and forecasting of water availability in this region. Here, we use a passive gamma ray sensor that measures snow water equivalent (SWE) and complementary meteorological instruments installed at 4962 m a.s.l. in the Nepal Himalayas to quantify the evolution of SWE and snow depth over a two year period. We assess the accuracy, spatial representativeness and the applicability of the SWE and snow depth measurements using time lapse camera imagery and field observations. The instrument setup performs well for snowpacks >50 mm SWE, but caution must be applied when interpreting measurements from discontinuous, patchy snow cover or those that contain lenses of refrozen meltwater. Over their typical ~6 month lifetime, snowpacks in this setting can attain up to 200 mm SWE, of which 10-15 % consists of mixed precipitation and rain-on-snow events. Precipitation gauges significantly underrepresent the solid fraction of precipitation received at this elevation by almost 40 % compared to the CS725. The application of sub-daily time lapse camera imagery can help to correctly interpret and increase the reliability and representativeness of snowfall measurements. Our monitoring approach provides high quality, continuous, near real time information that is essential to develop snow models in this data scarce region. We recommend that a similar instrument setup be extended into remote Himalayan environments to facilitate widespread snowpack monitoring and further our understanding of the high-altitude water cycle.